If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -8m = -4(6 + 4m) + -5m 2 + -8m = (6 * -4 + 4m * -4) + -5m 2 + -8m = (-24 + -16m) + -5m Combine like terms: -16m + -5m = -21m 2 + -8m = -24 + -21m Solving 2 + -8m = -24 + -21m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '21m' to each side of the equation. 2 + -8m + 21m = -24 + -21m + 21m Combine like terms: -8m + 21m = 13m 2 + 13m = -24 + -21m + 21m Combine like terms: -21m + 21m = 0 2 + 13m = -24 + 0 2 + 13m = -24 Add '-2' to each side of the equation. 2 + -2 + 13m = -24 + -2 Combine like terms: 2 + -2 = 0 0 + 13m = -24 + -2 13m = -24 + -2 Combine like terms: -24 + -2 = -26 13m = -26 Divide each side by '13'. m = -2 Simplifying m = -2
| 0.06(y-7)0.18y=0.16y-0.01y(50) | | 5n-6=30-n | | 75=m/25 | | 4y-13=9 | | 5x-2(x+7)= | | 75=m/6 | | 2(2x+1)=4x-5 | | 4x-10+90=90 | | 9(4x-1)=23 | | 7x+56=20 | | n+n^2=40 | | (1)/(2)(4x-6)=11 | | 72=-3+3(x-1)(x-1) | | 6x-2(-3x+7)=10 | | 3(g+4)=g+5 | | 12b+2=2(6b+3) | | (5+6x)+2= | | 6x+3=-3x+84 | | 4x-6x=-18 | | 6x+3=-33x+84 | | 3+p=20 | | 5(p-6)=2p | | 6-3(4x-1)=4x-7 | | 6x^2-27x+1=0 | | x=16x^2+3x-6 | | -x-13=-22 | | -7x+-16=-5 | | 3p=20 | | 6+2x=x+13 | | y+5=35 | | (24x^9)(y^12)/(3x6^3)(y^12) | | 6x-27x+1=0 |